2019
DOI: 10.1016/j.celrep.2018.12.081
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Macrophage-Derived Slit3 Controls Cell Migration and Axon Pathfinding in the Peripheral Nerve Bridge

Abstract: SummarySlit-Robo signaling has been characterized as a repulsive signal for precise axon pathfinding and cell migration during embryonic development. Here, we describe a role for Sox2 in the regulation of Robo1 in Schwann cells and for Slit3-Robo1 signaling in controlling axon guidance within the newly formed nerve bridge following peripheral nerve transection injury. In particular, we show that macrophages form the outermost layer of the nerve bridge and secrete high levels of Slit3, while migratory Schwann c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 43 publications
2
92
0
Order By: Relevance
“…In their study, Dun et al showed that Sox2 regulates Robo1 receptor expression in migrating SCs and that macrophages in the outermost layer of the nerve bridge secrete high levels of its ligand Slit3. Further gene ablation experiments confirm that Slit3/Robo1 repulsive signal is crucial for SC migration trajectory and correct nerve bridge formation following nerve transection [115]. Taken together these results suggest that the coordinated action of different cell types and the combined function of multiple axon guidance molecules is necessary for a correct nerve bridge tissue formation and precise axon targeting in the nerve bridge.…”
Section: Sox2 and Nerve Bridge Tissue Formationmentioning
confidence: 57%
See 2 more Smart Citations
“…In their study, Dun et al showed that Sox2 regulates Robo1 receptor expression in migrating SCs and that macrophages in the outermost layer of the nerve bridge secrete high levels of its ligand Slit3. Further gene ablation experiments confirm that Slit3/Robo1 repulsive signal is crucial for SC migration trajectory and correct nerve bridge formation following nerve transection [115]. Taken together these results suggest that the coordinated action of different cell types and the combined function of multiple axon guidance molecules is necessary for a correct nerve bridge tissue formation and precise axon targeting in the nerve bridge.…”
Section: Sox2 and Nerve Bridge Tissue Formationmentioning
confidence: 57%
“…Indeed, it has been shown that both pharmacological inhibition and genetical ablation of EphB2 resulted in significantly shorter and less organized regrowing axons as compared to untreated and wild type animals [26]. Moreover, Dun et al [115], showed that by regulating the Slit3/Robo1 pathway, Sox2 is also critical for SC migration in the nerve bridge and axon pathfinding after nerve injury. Indeed, this study shows how Sox2 loss of function leads to ectopic SC migration and to the inability to form proper SC cords connecting the nerves stumps [115].…”
Section: Sox2 and Nerve Bridge Tissue Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…These innate immune cells provide critical phagocytic functions . But additionally, these innate immune cells provide other functions essential to nerve regeneration, including re‐myelination and functional recovery, which are not yet entirely understood, After this Wallerian degeneration process is complete, SCs progressively assume long processes and align on the basal lamina of the intact distal nerve environment (bands of Bungner), providing a permissive growth environment for the regenerating axons that emerge from the proximal nerve stump . As axon growth proceeds from proximal to distal nerve, remyelination of the axons is initiated primarily by axon‐derived neuregulin‐1 signaling through SCs’ ErbB receptors .…”
Section: Biology Of Nerve Regeneration Across a Defectmentioning
confidence: 99%
“…The PLP-GFP mouse transgenic strain was used in this study (Mallon et al, 2002). Originally made to label oligodendrocytes in the central nervous system driven GFP expression by the mouse myelin PLP gene promoter, the PLP-GFP mice also express cytoplasmic GFP in both myelinating and non-myelinating Schwann cells of the peripheral nerves (Mallon et al, 2002;Stierli et al, 2018;Dun et al, 2019). All work involving animals was performed according to Home Office regulation under the UK Animals (Scientific Procedures) Act 1986.…”
Section: Animal Husbandry and Peripheral Nerve Surgerymentioning
confidence: 99%